Collagen Scaffolds: Iron Oxide‐Labeled Collagen Scaffolds for Non‐Invasive MR Imaging in Tissue Engineering (Adv. Funct. Mater. 6/2014). (February 2014) - Mertens, Marianne E.; Hermann, Alina; Bühren, Anne; Olde‐Damink, Leon; Möckel, Diana; Gremse, Felix; Ehling, Josef; Kiessling, Fabian; Lammers, Twan
<x xml:space="preserve">Abstract</x> The physical or chemical integration of ultrasmall superparamagnetic iron oxide nanoparticles into the 3D collagen‐based scaffold matrix of tissue‐engineered implants by T. Lammers and co‐workers on page 754 allows highly sensitive visualization and monitoring using MRI, and enables the longitudinal assessment of implant localization, function, remodeling, and resorption. Labeled scaffolds are shown to be highly biocompatible and suitable for tissue engineering applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>